Manuscript and Print in Late Medieval and Early Modern Britain Essays in Honour of Professor Julia Boffey (Cambridge Boydell & Brewer, 2019)
Literature, European and World Literature: General Interest
English
Keywords: Literature & literary studies; Literature, European and World Literature: General Interest